10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Background Physical activity has been shown to benefit students' academic achievement and engagement, yet the mechanisms remain unknown. In the present study, we aimed to examine the relationship between teacher caring behaviour and learning engagement among junior high school students in physical education, focusing on the potential mediating roles of psychological capital and learning motivation. Methods A total of 657 students participated in a cross-sectional survey (Study 1), and a 4-week teacher caring behaviour intervention was conducted in two classes (Study 2). Results The findings indicated that teacher caring behaviour was positively associated with learning engagement (r = 0.42, p < 0.01), psychological capital (r = 0.20, p < 0.01) and learning motivation (r = 0.31, p < 0.01); psychological capital (r = 0.42, p < 0.01) and learning motivation (r = 0.72, p < 0.01) were positively correlated with learning engagement. Teacher caring behaviour could predict learning engagement directly (B = 0.38, p < 0.01) or indirectly through three mediated pathways: psychological capital (B = 0.05, p < 0.01), learning motivation (B = 0.23, p < 0.01) and their chained effect (B = 0.03, p < 0.01). Four-week teacher caring behaviour may improve students' learning engagement, and psychological capital in hope (p = 0.003, ηp 2 = 0.101) and self-efficacy (p = 0.006, ηp 2 = 0.088) dimensions and learning motivation in external regulation (p = 0.009, ηp 2 = 0.078) dimension were improved. Conclusions This study suggested that teacher caring behaviour could positively predict junior high school students' leaning engagement in physical education classes, and psychological capital and learning motivation may play the mediating roles in the relationship between teacher caring behaviour and students' learning engagement in physical education classes. This study not only enriches the studies in the field of the relationship between teacher caring behaviour and learning engagement in physical education classes but also helps to understand the internal mechanisms.